2000
DOI: 10.1211/0022357001777414
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Erdosteine Against Hypochlorous Acid-induced Acute Lung Injury and Lipopolysaccharide-induced Neutrophilic Lung Inflammation in Mice

Abstract: The effect of erdosteine, a mucoactive drug, on hypochlorous acid (HOCl)-induced lung injury, and the lipopolysaccharide (LPS)-induced increase in tumour necrosis factor-alpha (TNF-alpha) production and neutrophil recruitment into the airway, was investigated. Male BALB/c mice were orally administered erdosteine (3-100 mgkg(-1)), ambroxol hydrochloride (ambroxol) (3-30 mgkg(-1)), S-carboxymethyl-L-cysteine (S-CMC) (100-600 mgkg(-1)) or prednisolone (10 mgkg(-1)), 1 h before intratracheal injection of HOCl or L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
2
15
0
3
Order By: Relevance
“…These findings indicate the potent free-radical scavenger properties of erdosteine reported in many previous studies (Hayashi et al, 2000; et al., 1991). The most common side-effect of this group of drugs (such as N-acetylcysteine) is gastric mucosa irritation due to the mucolytic affect, and this side-effect is rarely seen in erdosteine because the mucolytic effect of erdosteine emerges after hepatic metabolism (Giovanni et al, 1991).…”
Section: Discussionsupporting
confidence: 83%
“…These findings indicate the potent free-radical scavenger properties of erdosteine reported in many previous studies (Hayashi et al, 2000; et al., 1991). The most common side-effect of this group of drugs (such as N-acetylcysteine) is gastric mucosa irritation due to the mucolytic affect, and this side-effect is rarely seen in erdosteine because the mucolytic effect of erdosteine emerges after hepatic metabolism (Giovanni et al, 1991).…”
Section: Discussionsupporting
confidence: 83%
“…The activated T lymphocytes release cytokines including IL-2, IL-4 and IL-6, which participate in B lymphocyte activation. It has been reported that TNF-a levels in the serum, BALF and lung homogenate were increased in CB animals and patients [20,21]. The increased TNF-a could enhance T, B lymphocyte and AM reciprocity and exacerbate inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, treating rats with erdosteine attenuated the increase in the tissue levels of MPO and MDA caused by the I/R condition. Hayashi et al [17] reported that erdosteine inhibited neutrophil infiltration in mice intratracheally treated with LPS. In addition, it has been suggested that erdosteine exhibits antioxidant properties by blocking production of ROS in human neutrophils and suppresses the oxidative burst of human polymorphonuclear leukocytes [3].…”
Section: Discussionmentioning
confidence: 99%